Healthcare personnel experiences implementing carbapenem-resistant Enterobacterales infection control measures at a ventilator-capable skilled nursing facility—A qualitative analysis. (21st August 2022) - Rynkiewich, Katharina R.; Makhija, Jinal; Froilan, Mary Carl M.; Benson, Ellen C.; Han, Alice; Trick, William E.; Weinstein, Robert A.; Hayden, Mary K.; Lin, Michael Y.
Abstract: Objective: Ventilator-capable skilled nursing facilities (vSNFs) are critical to the epidemiology and control of antibiotic-resistant organisms. During an infection prevention intervention to control carbapenem-resistant Enterobacterales (CRE), we conducted a qualitative study to characterize vSNF healthcare personnel beliefs and experiences regarding infection control measures. Design: A qualitative study involving semistructured interviews. Setting: One vSNF in the Chicago, Illinois, metropolitan region. Participants: The study included 17 healthcare personnel representing management, nursing, and nursing assistants. Methods: We used face-to-face, semistructured interviews to measure healthcare personnel experiences with infection control measures at the midpoint of a 2-year quality improvement project. Results: Healthcare personnel characterized their facility as a home-like environment, yet they recognized that it is a setting where germs were 'invisible' and potentially 'threatening.' Healthcare personnel described elaborate self-protection measures to avoid acquisition or transfer of germs to their own household. Healthcare personnel were motivated to implement infection control measures to protect residents, but many identified structural barriers such as understaffing and time constraints, and some reported persistent preference for soap and water. Conclusions: Healthcare personnel in vSNFs, from management to frontline staff, understood germ theory and the significance of multidrug-resistant organism transmission. However, their ability to implement infection control measures was hampered by resource limitations and mixed beliefs regarding the effectiveness of infection control measures. Self-protection from acquiring multidrug-resistant organisms was a strong motivator for healthcare personnel both outside and inside the workplace, and it could explain variation in adherence to infection control measures such as a higher hand hygiene adherence after resident care than before resident care.